A Gastroenterologist's Perspective of The Medical Management of Patients with Crohn's Disease and Ulcerative Colitis. (1st February 1996) - Thomson, ABR
Abstract : Medical therapy in patients with inflammatory bowel disease (IBD) has specific objectives that need to be remembered when considering any form of intervention. These objectives include to improve the quality of life, to improve symptoms, to improve nutrition and reduce the risk of nutritional deficiencies, to reduce the frequency and severity of recurrences, to reduce complications, including the need for surgery, and to cure the disease. Medical therapy potentially helps to achieve all of these objectives for sufferers of IBD, except the last one – until the pathogenesis of the recurrent or continuous episodes of bowel inflammation is better understood, this last objective will remain "a riddle, wrapped in a mystery, inside an enigma".